The "Anatomical Balance Correction" for Secondary Cleft Lip Nasal Deformities. Issue 8 (November 2016) - Bertossi, Dario; Corega, Claudia; Boccieri, Armando; Procacci, Pasquale; Mortellaro, Carmen; Nocini, Pierfrancesco
Abstract : Secondary cleft lip nasal deformities corrective procedures are still a major concern for the maxillofacial surgeons.